Prevalence of Asymptomatic Bacteriuria in Antenatal Women Coming to NRIMC&GH (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s):The aim of the study was to determine the prevalence of asymptomatic bacteriuria in pregnant women attending the antenatal OPD and to treat them. Also to identify the organisms causing asymptomatic bacteriuria and the risk factors in pregnant women.Materials and Methods: The present observational study was conducted in the Department of Obstetrics, NRI Medical College, Chinakakani, Mangalagiri from Aug-2012 to Aug-2014. Material for the study consisted of 100 urine samples obtained from asymptomatic 100 pregnant women in their first antenatal visit. The study group consisted of cases from in and around Mangalagiri, attending antenatal OPD, NRI Medical College, Chinakakani. Each patient was first asked whether she had any symptom of urinary tract infection such as dysuria, urgency, haematuria, loin pain and fever. After ascertaining that she was asymptomatic, preliminary data on maternal age, gravidity, parity and period of gestation were collected on a predesigned proforma. Detailed history about previous antenatal check-up, hypertension were also taken. A clean-catch midstream urine sample was collected and MacConkey agar, Blood agar plates were used for culture .Bacterial counts were done to determine the number of microorganisms per millilitre.Antimicrobial susceptibility testing was done for the isolates by the Kirby-Bauer method (disc diffusion).Results: The prevalence of asymptomatic bacteriuria in the study group was 15%.Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus saprophyticus, Staphylococcus aureus were the isolates in the study group. Isolates showed maximum susceptibility to gentamycin followed by cefotaxime, nitrofurantoin and cotrimoxazole. They showed high degree of resistance to cephalexin and ceftriaxone. All the asymptomatic pregnant women with significant bacteriuria were treated and asked to come back after 7-10 days for repeat culture and susceptibility testing, which was done as a part of follow-up.Conclusion: Increasing gestational period showed increase in the incidence of asymptomatic bacteriuria and also increased incidence was seen in the pregnants with anaemia. Routine antenatal screening for asymptomatic bacteriuria should be implemented and treatment of those showing bacteriuria must be practiced to prevent adverse perinatal outcome. Untreated asymptomatic bacteriuria progresses to pyelonephritis (13-27%). Therefore, routine screening for bacteriuria is recommended during pregnancy.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 30-36